2017
DOI: 10.1021/acs.cgd.7b00325
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Nanoscale Step Dynamics in High-Temperature Solution-Grown Single Crystal 4H-SiC via In Situ Confocal Laser Scanning Microscope

Abstract: Nanoscale understanding of high-temperature crystal growth dynamics in solution has been a challenge to be tackled by many researchers engaged in investigating solution processes for bulk single crystal growth. Here we propose a new approach to in situ observation at a buried solid/liquid interface in high-temperature solution using a conventional confocal laser scanning microscope. In the solution growth of 4H-SiC with Si−Ni based alloy flux as a model system, we show the ability to quantitatively analyze ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…At first place, it is seen that in every case studied bunch size always achieves, sooner or later, a power law dependence on the time with β = 1/2. We could speculate on this observation further in a growth model of single crystal SiC growing further in Si− Ni flux conditions, Onuma et al 14 found step bunching to occur in diffusion-limited conditions but not in the kinetics limited ones. Based on our results, we could suggest that in the KL case the process maybe was not carried to long enough times that would permit the observation of SB.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…At first place, it is seen that in every case studied bunch size always achieves, sooner or later, a power law dependence on the time with β = 1/2. We could speculate on this observation further in a growth model of single crystal SiC growing further in Si− Ni flux conditions, Onuma et al 14 found step bunching to occur in diffusion-limited conditions but not in the kinetics limited ones. Based on our results, we could suggest that in the KL case the process maybe was not carried to long enough times that would permit the observation of SB.…”
Section: Resultsmentioning
confidence: 94%
“…In a rather different context, the interest in SB is closely connected with its, sometimes dramatic, impact on the processes of nanostructure layer-by-layer epitaxial growth as realized in various deposition techniques having their industrial realizations. Nowadays, the keyword step bunching bridges studies on material systems as diverse as CH 3 NH 3 PbI 3 , GaN, AlN, AlGaN, SiC, graphene, , PTCDA (perylene tetracarboxylic acid dianhydride)/Ag, pyronaridine/heme, SrRuO 3 /(001) SrTiO 3 , KDP, ferritin, etc. The phenomenon however is not limited to the epitaxial growth only.…”
Section: Introductionmentioning
confidence: 99%
“…Since the resolution is determined by the position of the beam rather than the pixel size of the detector, nanometer-level resolution digital images of any material can be generated by using LSM. By analyzing the intensity of the returned laser light relative to the zposition of the laser, nanometer-level heights can also be measured, and surface topography can be provided at any selected specimen micro areas [33][34][35][36].…”
Section: Laser Scanning Microscopy (Lsm)mentioning
confidence: 99%
“…The data of the calculated carbon solubility in Si 0.6 Cr 0.4 solvent was provided from the Mitani research group [10]. The experimentally obtained carbon contents were compared with the solid line, which originated from phase diagrams of the Si-Cr-C systems calculated by Thermo-Calc (Thermo-Calc Software, Sweden) based on the CALPHAD method [10][11][12]. The thermodynamic dataset and Gibbs energy functions for Si, Cr, and C were obtained from the SGTE database (SSOL5) implemented in Thermo-Calc.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically calculated carbon solubilities in Si-Cr solvents have been reported using CALPHAD (calculation of phase diagrams) methods and have been relied upon in the solution growth of SiC [3,[10][11][12]. CAL-PHAD is a useful method for assigning a number to carbon solubility in a multicomponent system.…”
Section: Introductionmentioning
confidence: 99%